Decreasing the mass indices of gas turbine engines regenerators by means of choosing rational parameters - Gorbov, Viktor; Solomonuk, Denis (Eastern-European Journal of Enterprise Technologies, 2016)
The purpose of the conducted research was to develop a method for determining parameters of GTE regenerator, which would ensure at the initial stages of designing a minimum mass of the heat exchanger with the assigned values of efficiency. We obtained dependences that establish relationships between the regenerator and the GTE, which allow analyzing the influence of effectiveness and pressure losses in regenerator on the efficiency of GTE and the mass of the regenerator. Relationship between parameters of the regenerator and performance efficiency of regenerative GTE was described by functional dependence, where energy parameters of the regenerator are collected in a single complex. It was established that the magnitude of effectiveness of the regenerator is associated with efficiency by inversely proportional function, and pressure losses – by linear function. Effectiveness of the regenerator is associated with the mass of the heat exchanger and the geometry of heat exchange surface by exponential dependence, and relative pressure losses – by algebraic irrational function. Based on these dependences, the algorithm for selecting rational energy and geometrical parameters of regenerators of GTE was developed. It was found that by selecting rational values of effectiveness of regenerator and pressure losses, it is possible to provide for a significant decrease in mass of the regenerator with a constant value of performance efficiency of GTE. The obtained results of calculations of regenerators of GTE with different structural solutions allow a designer engineer to choose rational values of effectiveness of the regenerator, pressure losses, and initial gas temperature. Comparison of complex regenerative GTE by the mass of regenerator at constant values of performance efficiency was conducted. Based on the analysis of results of calculations, the stage dependence of specific mass of regenerator on the assigned increase in performance efficiency of regenerative GTE was obtained, which gives the possibility to estimate the mass of tubular regenerator at the initial stages of designing. Implementation of the obtained results into the practice of designing regenerative GTE will make it possible to ensure the choice of their rational parameters and to decrease the time of designing.